Degraded DNA samples made informative by using superprimers. - Mautner, Martin E. (2017)
The use of long ssDNA polynucleotides in PCR of degraded DNA samples can discriminate Short Tandem Repeat (STR) genotypes otherwise missed by current commercial kits.